Analisis Fenomena "Purbaya Effect": Transformasi Psikologi Pasar dan Implikasi Kebijakan Fiskal Agresif di Indonesia - Ronni Haga; Sunaryo Neneng (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study analyzes the economic phenomenon known as the "Purbaya Effect" in the Indonesian capital market during the second half of 2025. This phenomenon is characterized by a significant surge in the Jakarta Composite Index (IHSG), which broke the All-Time High (ATH) record 21 times within four months following the appointment of Purbaya Yudhi Sadewa as Minister of Finance. Using a mixed-methods approach combining quantitative market data analysis and qualitative policy review, this research finds that the "Purbaya Effect" is driven by aggressive liquidity injection policies (Rp 200 trillion), institutional trust built during his tenure at LPS, and strong narrative economics. However, this study also identifies significant risks related to exchange rate volatility and potential economic overheating. The findings suggest that while the "Purbaya Effect" successfully restored short-term investor confidence, long-term sustainability depends on the balance between growth acceleration and macroeconomic stability.